2019
DOI: 10.1021/acs.jafc.9b02313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genotype and Harvest Time on the Cynara cardunculus L. Sesquiterpene Lactone Profile

Abstract: The excessive and inappropriate application of herbicides has caused environmental pollution. The use of allelochemicals as bioherbicides could provide a solution to this problem. The allelopathic activity of Cynara cardunculus L. has been studied previously, and sesquiterpene lactones (STLs) were identified as the most relevant allelochemicals. The goal of the study reported here was to investigate the effect of six genotypes and three harvest times on the qualitative and quantitative composition of STLs in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
(88 reference statements)
8
37
0
Order By: Relevance
“…In "Spagnolo" prolonged salinity determined a slight increase in cynaropicrin (Figure S2). Several authors reported cynaropicrin accumulation in cardoon and artichoke as localized in specific tissues and mostly dependent on developmental stages, genotype, and harvesting time [26,51]. Moreover, in other Asteraceae high de novo production of STLs in leaves or their release from glandular trichomes is usually associated to a feeding attack from chewing insects or birds, indicating that a repelling flavor can be a protective mechanism [28].…”
Section: Discussionmentioning
confidence: 99%
“…In "Spagnolo" prolonged salinity determined a slight increase in cynaropicrin (Figure S2). Several authors reported cynaropicrin accumulation in cardoon and artichoke as localized in specific tissues and mostly dependent on developmental stages, genotype, and harvesting time [26,51]. Moreover, in other Asteraceae high de novo production of STLs in leaves or their release from glandular trichomes is usually associated to a feeding attack from chewing insects or birds, indicating that a repelling flavor can be a protective mechanism [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new C. cardunculus allelochemicals (cynaratriol, deacylcynaropicrin, 11,13-dihydro-deacylcynaropicrin and pinoresinol) were purified [141]. Then, after the development of a new ultra-high-performance liquid chromatography-tandem mass spectrometry analysis method, the influence of genotype and harvest time was studied on the phytotoxicity, amount and composition of its allelochemicals [142].…”
Section: Technique Allelopathic Source Target Weeds Description Refermentioning
confidence: 99%
“…Cardoon leaf extracts are also known for their allelopathic activities. Allelopathy is the direct or indirect effect of a plant over a target species (plants, algae, bacteria, or fungus) through the release of chemical compounds, allelochemicals, into the environment [61,67,68]. The allelochemicals can be integrated with weed management and can be introduced into the environment through volatilization from the aboveground parts of the plant, root exudation, foliar leaching, or plant residue decomposition [61,[67][68][69][70].…”
Section: Phytotoxic and Allelopathic Propertiesmentioning
confidence: 99%
“…Allelopathy is the direct or indirect effect of a plant over a target species (plants, algae, bacteria, or fungus) through the release of chemical compounds, allelochemicals, into the environment [61,67,68]. The allelochemicals can be integrated with weed management and can be introduced into the environment through volatilization from the aboveground parts of the plant, root exudation, foliar leaching, or plant residue decomposition [61,[67][68][69][70]. Phenolic compounds and sesquiterpene lactones are the most common examples of allelochemicals and can be found in different parts of plants, such as leaves, roots, stems, rhizomes, seeds, flowers, and pollen [69,71].…”
Section: Phytotoxic and Allelopathic Propertiesmentioning
confidence: 99%